Finance and Development, June 1980. (Finance and Development; Finance and Development, 1980)
This paper highlights that in a shift of policy, the World Bank decided to finance directly health projects in developing countries. Under its old policy, formulated in 1974, health components providing basic health care for low-income individuals were incorporated into projects in other sectors, such as agriculture and rural development, urban development, and water supply and sewerage. Lending for such components will continue. After reviewing the World Bank's experience in financing health-related activities in 44 countries, the report recommends the adoption of a three-tier pyramidal structure for delivery of health services, adapted to local conditions.